Socio-Economic Influence of Remittances on Households In The Patihani Buffer Zone, Chitwan National Park, Nepal - Dhakal, Keshav Raj (The Third Pole: Journal of Geography Education, 2024)
This paper explores the socio-economic influence of remittances on households in the Patihani Buffer Zone, Chitwan National Park, Nepal. Remittances are a significant income source for many households in developing countries, with Nepal being among the highest recipients of these remittances as a share of GDP. The inflow of funds plays a vital role in shaping the socio-economic landscape of communities. Two hundred fifty households from the Patihani buffer zone were selected for a study on the socioeconomic impact of remittance using questionnaire surveys. The household was the sampling unit for a questionnaire survey, which was analyzed using SPSS and Excel software, revealing descriptive statistics on the impact of remittance. Remittances are an important income source for households, enhancing their socio-economic status, as perceived by the respondents, both before and after migration. The income not only increases household consumption but also has significant impacts on education, healthcare, and local economic investments. However, labor migration has had some negative socio-economic effects on families. The finding suggests that understanding these impacts is crucial for creating policies that promote sustainable growth while maintaining the ecological integrity of buffer zones like the Patihani Buffer Zone Area.